Loanwords from Spanish in a Junin-Huanca Quechua Dictionary - Ferrell Ramírez, Marco Aurelio (2016)
When two languages come in contact, an interplay invariably takes place in which one language receives influences from the other, both lexical and phonological. Rodolfo Cerrón’s bilingual dictionary (Diccionario Quechua Junín-Huanca) is a relevant example, as it presents a wide range of samples of Spanish words adapted to the Quechua phonological patterns. So, a Spanish stressed vowel can be interpreted as a long vowel (lado > laadu), Spanish [o] is interpreted as a close vowel [u] (gallo > gaallu), Spanish dipthongs can be simplified (antiguo > antiibu, apuesta > apusti), Spanish consonants can be changed (horqueta > hurhita, suegra > suydra), etc.